2011
DOI: 10.1177/0959354310377821
|View full text |Cite
|
Sign up to set email alerts
|

Definitions of schizophrenia, 1908–1987: The failed essentialism

Abstract: This work examines the historical conceptualization of schizophrenia through definition from 1908–1987. Rather than reveal an essentialist definition of schizophrenia in North America, it reveals a history of varying and competing professional definitions. It demonstrates and historically contextualizes how widespread conceptual instability and disagreement over the nature of the concept gave rise to a new, but still contested, theoretical emphasis on operational definitions. As made manifest through definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Note, however, that the diversity of ideas about the basic definition of schizophrenia throughout the 20th century cannot be understated—despite the fact that the lack of attention to history in medico-clinical discourse sometimes leads to a kind of collective forgetting once new diagnostic concepts are brought into consensus (see Kuhn, 1962/1996). As the authors of one conceptual history of the diagnosis concluded, “the history of schizophrenia can be best described as the history of a set of research programmes running in parallel rather than serialism and each based on a different concept of disease, of mental symptom and of mind” (Berrios, Luque, & Villagrán, 2003, p. 111; see also Kurtz, 2015; Marsella, 2016; McNally, 2012). Even mid-century psychoanalytic theories about schizophrenia (and psychosis more broadly) were notably diverse, ranging from classic Freudian ideas about a form of primary narcissism in which the libido withdraws from the world and recathects onto the ego (Freud, 1914/1957), to ego psychologists’ supposition of a dissolution in ego boundaries (see Ophir, 2015, for an overview), to Searles’ (e.g., 1965) and Fromm-Reichmann’s (e.g., 1952) interpretations of the life-historical meanings in putatively anomalous behaviors, to Sullivan’s (e.g., 1962) insights about interpersonal etiology, loneliness in particular.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Note, however, that the diversity of ideas about the basic definition of schizophrenia throughout the 20th century cannot be understated—despite the fact that the lack of attention to history in medico-clinical discourse sometimes leads to a kind of collective forgetting once new diagnostic concepts are brought into consensus (see Kuhn, 1962/1996). As the authors of one conceptual history of the diagnosis concluded, “the history of schizophrenia can be best described as the history of a set of research programmes running in parallel rather than serialism and each based on a different concept of disease, of mental symptom and of mind” (Berrios, Luque, & Villagrán, 2003, p. 111; see also Kurtz, 2015; Marsella, 2016; McNally, 2012). Even mid-century psychoanalytic theories about schizophrenia (and psychosis more broadly) were notably diverse, ranging from classic Freudian ideas about a form of primary narcissism in which the libido withdraws from the world and recathects onto the ego (Freud, 1914/1957), to ego psychologists’ supposition of a dissolution in ego boundaries (see Ophir, 2015, for an overview), to Searles’ (e.g., 1965) and Fromm-Reichmann’s (e.g., 1952) interpretations of the life-historical meanings in putatively anomalous behaviors, to Sullivan’s (e.g., 1962) insights about interpersonal etiology, loneliness in particular.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The history of the diagnosis of schizophrenia in the US reveals a history of diverse and competing definitions (McNally, 2012). In 1911, when Bleuler described the schizophrenia concept in his influential book Dementia Praecox or the Group of Schizophrenias, the US psychiatry was under heavy influence of Adolf Meyer's (1866Meyer's ( -1950 works (Andreasen, 1989).…”
Section: The Emergence and Rise Of Schizophrenia In The Usmentioning
confidence: 99%
“…In the last three decades, the history of diagnostic classifications in psychiatry has been recognized as a privileged means of access to the vicissitudes, tensions, conflicts and negotiations inherent to the configuration of a scientific and professional field, also bringing significant contributions to conceptual history (Berrios, 1999;Berrios & Porter, 1995;Engstrom & Weber, 2007;McNally, 2012McNally, , 2013Venancio, 2010). 1 In this paper, we begin by briefly describing the history of the concept of schizophrenia, especially in the US.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the numerous definitions of schizophrenia that fluctuated throughout the 20 th century, ranging from Kraepelinian and Bleulerian to psychodynamic and anti-psychiatric, were hardly reconcilable. The disagreements, confusions and inconclusiveness of debates on the ontological status of schizophrenia lead to the abandonment of competing individual definitions in favor of operational description, which was a pragmatic solution to the long-standing problem (McNally, 2012). Unintentionally, however, the operational approach of the DSMs led to the "death" of phenomenological psychopathology in the clinical setting (Andreasen, 2007).…”
Section: Introductionmentioning
confidence: 99%